VARIETY AND PRINCIPLES OF COOPERATION OF DOUBLE CROWNS OF TELESCOPIC CONNECTIN - Yu. Ye. Tarashevska; Ye. G. Shyyan (Український стоматологічний альманах)
For today, problem of fixing of partial removable prostheticappliances, and more precisely it remains not fully decidedthe term of endurance and worn down of friction propertiesof telescopic connections. Therefore, the search for improvement of fixative properties of telescopic connection sremains actual.